Collective memory in traditional bèsèk packaging: impact on buyer perception at Omah Jenang Blitar - Andika Agung Sutrisno; Bambang Sunarto; Pujiyanto Pujiyanto (International Journal of Visual and Performing Arts, 2024)
This research examines the design of basic packaging for traditional culinary products at Omah Jênang Kêtan Kelapa Sari Blitar, using it as a case study. It critically evaluates the relationship between traditional culinary products, effective packaging, and labels. Bèsèk packaging not only protects culinary products from damage but also enhances their appeal with a natural and traditional look. The packaging label provides essential information about the product, including composition, expiration date, and storage instructions. The aim is to evaluate how traditional packaging influences consumer perceptions and to understand the relationship between traditional culinary products and their packaging and labels. This study offers insights into the significance of preserving traditional elements in packaging design and how these elements can inform more effective marketing strategies. A qualitative data analysis method is employed to assess the packaging design used by Omah Jênang Kêtan Kelapa Sari Blitar, focusing on visual stimuli and their impact on consumer memory. The research found that good packaging design fosters emotional bonds between traders and buyers, rooted in traditional collective memories, which enhances the durability and sustainability of the packaging. Additionally, Bèsèk's packaging design connects with collective memory, associated with romance and stories of past events, increasing consumer interest in recalling these experiences. The findings provide insights into how various packaging designs influence consumer perceptions and feelings toward traditional culinary products. This research underscores the importance of visual attributes in packaging design, highlighting their ability to stimulate consumer perceptions of collective memory and create meaningful, memorable packaging experiences.